Meta Analysis: The Effects of Attitude, Spouse Support, and Education Level on Men Participation in Male Contraceptive Use - Yuliana Yuvrista; Argyo Demartoto; Bhisma Murti (Masters Program in Public Health, Sebelas Maret University, 2023)
Background: One of the government's strategies to support women's equal rights is to issue a policy in which people of reproductive age, both men and women, are expected to participate in the Family Planning program as an effort to raise awareness, willingness and ability of the community to improve their welfare independently. This study aims to analyze the influence of attitude, partner support, and level of education on men's participation in the use of contraception. Subjects and Method: This was a systematic review and meta-analysis. The study population was men of reproductive age. Intervention= positive attitude, strong partner support, and high education. Comparison= negative attitude, weak support, and low education. Outcome= the use of contraceptives. Data search was carried out systematically using electronic databases from Pubmed, Google Scholar, Europe PMC, Science Direct, and Springer Link. Keywords used “Attitude” AND “Partner support” OR “Discuss with partner” AND “Educational status” OR “Educational level” AND “Men participation” OR “Men Involvement” AND “Contraception” OR “Family Planning” OR “Vasectomy” OR “Condom”. The selection of primary articles used the PRISMA flowchart which was analyzed using Review Manager 5.3. Results: Six studies showed that men with a positive attitude were 3.69 times more likely to use contraception than men with a negative attitude (aOR= 3.69; 95% CI= 2.23 to 6.09; p<0.001). Six studies showed that men with strong partner support are 2.48 times more likely to use contraception than men with weak partner support (aOR= 2.48; 95% CI= 2.04 to 3.02; p<0.001). Eight studies showed that men with a high level of education increased the likelihood of male contraceptive use (aOR= 2.07; CI 95%= 1.45 to 2.96). Conclusion: Positive attitude, strong partner support, and a high education increase the use of male contraceptives. Keywords: attitude, partner support, level of education, contraception. Correspondence: Yuliana Yuvrista. Masters Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta, Central Java 57126, Indonesia. Email: yulianayuvrista031@gmail.com. Mobile: +6285333622880.